PERAN KONSELING INDIVIDU DENGAN ACCEPTANCE AND COMMITMENT THERAPY DALAM MENANGANI KORBAN BODY SHAMING MAHASISWI PRODI MANAJEMEN UNIVERSITAS SLAMET RIYADI SURAKARTA TAHUN AKADEMIK 2024/2025 - Asri Vina Loza; Heru Sri Suryanti, Hera; Jawandi, Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study was to determine how individual counseling services using the Acceptance and Commitment Therapy approach can reduce the negative impact on victims of body shaming among students in the Management Study Program at UNISRI. This research was conducted at Slamet Riyadi University, Surakarta. The subjects were students in the Management Study Program at Slamet Riyadi University, Surakarta. This study was a Guidance and Counseling Action Research (PTBK) conducted in three cycles. Each cycle consisted of four stages: Planning, Action, Observation, and Reflection. Data collection techniques used in this study were observation, interviews, and documentation.Based on the results of the pre-cycle actions, 90.6% identified the characteristics of body shaming victims. In cycle I, there was a decrease in the characteristics of body shaming victims by 77.33%, the results of cycle II actions obtained a decrease in the characteristics of body shaming victims by 58%, and the results of cycle III actions obtained a decrease in the characteristics of body shaming victims by 20%. It can be concluded that the role of individual counseling services with the Acceptance and Commitment Therapy approach is able to reduce the negative impacts for victims of body shaming in the management study program students of Slamet Riyadi University Surakarta in the 2024/2025 Academic Year.